Impact of Comorbidities and Age on Cause‐Specific Mortality in Postmenopausal Patients with Breast Cancer - Derks, Marloes G.M.; Velde, Cornelis J.H.; Giardiello, Daniele; Seynaeve, Caroline; Putter, Hein; Nortier, Johan W.R.; Dirix, Luc Y.; Bastiaannet, Esther; Portielje, Johanneke E.A.; Liefers, Gerrit‐Jan (The oncologist (Dayton, Ohio), 2019)
Background The aim was to study the impact of comorbidities and age on breast cancer mortality, taking into account competing causes of death. Subjects, Materials, and Methods Cohort analysis of Dutch and Belgian patients with postmenopausal, early hormone receptor‐positive breast cancer included in the Tamoxifen and Exemestane Adjuvant Multinational (TEAM) trial between 2001 and 2006. This is a randomized controlled trial of patients who had completed local treatment with curative intent and were randomized to receive exemestane for 5 years, or sequential treatment of tamoxifen followed by exemestane for a duration of 5 years. Patients were categorized by number of comorbidities (no comorbidities, 1–2 comorbidities, and >2 comorbidities) and age (<70 years and ≥70 years). Main outcome was breast cancer mortality considering other‐cause mortality as competing event; cumulative incidences were calculated using the Cumulative Incidence Competing Risk Methods, and the Fine and Gray model was used to calculate the effect of age and comorbidities for the cause‐specific incidences of breast cancer death, taking into account the effect of competing causes of death. Results Overall, 3,159 patients were included, of which 2,203 (69.7%) were aged <70 years and 956 (30.3%) were aged ≥70 years at diagnosis. Cumulative incidence of breast cancer mortality was higher among patients ≥70 without comorbidities (22.2%, 95% CI, 17.5–26.9) compared with patients <70 without comorbidities (15.6%, 95% CI, 13.6–17.7, reference group), multivariable subdistribution hazard ratio (sHR) 1.49 (95% CI, 1.12–1.97, p = .005) after a median follow‐up of 10 years. Use of chemotherapy was lower in older patients (1%, irrespective of the number of comorbidities) compared with younger patients (50%, 44%, and 38% for patients with no, 1–2, or >2 comorbidities, p < .001). Conclusion Older patients without comorbidities have a higher risk of dying due to breast cancer than younger counterparts, even when taking into account higher competing mortality, while use of chemotherapy in this group was low. These findings underline the need to take into account comorbidities, age, and competing mortality in the prognosis of breast cancer for accurate decision making. Implications for Practice Older patients without comorbidity are at increased risk of dying from breast cancer, despite a higher other‐cause mortality. This study shows that including age and comorbidity for the assessment of breast cancer mortality and other‐cause mortality is indispensable for treatment decision making in older patients. Future prognostic tools for breast cancer prognosis should incorporate these items as well as risk of toxicity of adjuvant chemotherapy to adequately predict outcomes to optimize personalized treatment for older patients with early breast cancer. This analysis of TEAM trial data focuses on the effects of comorbidities and age on breast cancer mortality and other cause mortality after 10 years of follow‐up, taking into account competing causes of death.